Molecular and Biochemical Analysis of the Estrogenic and Proliferative Properties of Vitamin E Compounds - Khallouki, Farid; de Medina, Philippe; Caze-Subra, Stéphanie; Bystricky, Kerstin; Balaguer, Patrick; Poirot, Marc; Silvente-Poirot, Sandrine (Frontiers in Oncology, 2016)
Tocols are vitamin E compounds that include tocopherols (TP) and tocotrienols (TT). These lipophilic compounds are phenolic antioxidants and are reportedly able to modulate estrogen receptor β (ERβ). We investigated the molecular determinants that control their estrogenicity and effects on the proliferation of breast cancer cells. Docking experiments highlighted the importance of the tocol phenolic groups for their interaction with the ERs. Binding experiments confirmed that they directly interact with both ERα and ERβ with their isoforms showing potencies in the following order: δ-Tocols>γ-Tocols>α-Tocols. We also found that tocols activated the transcription of an estrogen-responsive reporter gene that had been stably transfected into cells expressing either ERα or ERβ. The role of the phenolic group in tocol-ER interaction was further established using δ-tocopherylquinone, the oxidized form of δ-TP, which had no ER affinity and did not induce ER-dependent transcriptional modulation. Tocol activity also required the AF1 transactivation domain of ER. We found that both δ-TP and δ-TT stimulated the expression of endogenous ER-dependent genes. However, whereas δ-TP induced the proliferation of ER-positive breast cancer cells but not ER-negative breast cancer cells, δ-TT inhibited the proliferation of both ER-positive and ER-negative breast cancer cells. These effects of δ-TT were found to act through the down regulation of HMG-CoA reductase activity, establishing that ERs are not involved in this effect. Altogether these data show that the reduced form of δ-TP has estrogenic properties which are lost when it is oxidized, highlighting the importance of the redox status in its estrogenicity. Moreover, we have shown that δ-TT has antiproliferative effects on breast cancer cells independently of their ER status through the inhibition of HMG-CoA reductase. These data clearly show that TPs can be discriminated from TTs according to their structure.